2005
DOI: 10.1038/sj.bjp.0706367
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endogenous hydrogen sulfide formation reduces the organ injury caused by endotoxemia

Abstract: 1 Hydrogen sulfide (H 2 S) is a naturally occurring gaseous transmitter, which may play important roles in normal physiology and disease. Here, we investigated the role of H 2 S in the organ injury caused by severe endotoxemia in the rat. 2 Male Wistar rats were subjected to acute endotoxemia (Escherichia coli lipopolysaccharide (LPS) 6 mg kg À1 intravenously (i.v.) for 6 h) and treated with vehicle (saline, 1 ml kg À1 i.v.) or DLpropargylglycine (PAG, 10-100 mg kg À1 i.v.), an inhibitor of the H 2 S-synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
104
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(117 citation statements)
references
References 32 publications
7
104
1
3
Order By: Relevance
“…H 2 S has been proposed as a potential endogenous ligand for K ATP channels and induces K ATP channel-mediated vasorelaxation [28] in several vascular tissues, promoting speculation that H 2 S may play a role in endotoxic shock, an important form of acute inflammation, as mentioned. Indeed, early studies using cecal ligation and puncture (CLP) or injection of bacterial LPS into rats or mice significantly increased the expression of CSE and CBS and H 2 S synthesis in plasma, vascular tissues, lung, liver, kidney and pancreas [21,[29][30][31][32]. This suggested that, as with • NO synthesis (via inducible nitric oxide synthase [iNOS]), H 2 S synthesis is also an inducible phenomenon.…”
Section: H 2 S and Acute Whole-body Inflammation (Sepsis)mentioning
confidence: 99%
See 2 more Smart Citations
“…H 2 S has been proposed as a potential endogenous ligand for K ATP channels and induces K ATP channel-mediated vasorelaxation [28] in several vascular tissues, promoting speculation that H 2 S may play a role in endotoxic shock, an important form of acute inflammation, as mentioned. Indeed, early studies using cecal ligation and puncture (CLP) or injection of bacterial LPS into rats or mice significantly increased the expression of CSE and CBS and H 2 S synthesis in plasma, vascular tissues, lung, liver, kidney and pancreas [21,[29][30][31][32]. This suggested that, as with • NO synthesis (via inducible nitric oxide synthase [iNOS]), H 2 S synthesis is also an inducible phenomenon.…”
Section: H 2 S and Acute Whole-body Inflammation (Sepsis)mentioning
confidence: 99%
“…Conversely, administration of the CSE inhibitor propargylglycine (PAG; see later) to LPS-or CLPtreated animals decreased plasma H 2 S levels significantly, tissue edema and increased survival [21,29,30], suggesting that elevated plasma H 2 S was likely to be associated with the hemodynamic collapse observed in septic shock [21]. It should be noted that the protective effects of PAG may be independent of the improvement of hemodynamics (or CSE), since PAG treatment alone did not alter systemic blood pressure or affect LPS-induced hypotension but did significantly reduce the hepatic, pancreatic and neuromuscular damage induced by LPS [31]. In hemorrhagic shock however, blood withdrawal led to significantly increased liver (but not kidney) and plasma levels of H 2 S, and pretreatment of rats with PAG or b-cyanoalanine (BCA; a reversible inhibitor of CSE) reduced liver H 2 S synthesis and partially restored systemic blood pressure [20,35].…”
Section: H 2 S and Acute Whole-body Inflammation (Sepsis)mentioning
confidence: 99%
See 1 more Smart Citation
“…3), metabolic hibernation (4,5), protection from ischemia/reperfusion injury (6 -10), oxygen sensing (11), vasodilatation (12,13), and promotion of angiogenesis (14). In common with nitric oxide, H 2 S is also implicated as both a pro- (15)(16)(17)(18) and antiinflammatory (18 -21) molecule in innate immune cells. Although the role of H 2 S signaling has been characterized in many other tissues and systems, it is unclear what role it plays in the regulation of the adaptive immune system.…”
mentioning
confidence: 99%
“…12 Besides, experimental data in animals show that an enhanced production of endogenous H 2 S contributes to the pathophysiology of the organ injury associated with sepsis and shock. 13,14 Pharmacological effects of H 2 S are essentially related to two distinct mechanisms: first, the ability to activate/open membrane K ATP channels 7 and second, and the modulation of gene transcription by the activation of different signaling pathways. Many studies, focused on myocardial protection, have shown the cardioprotective effects of H 2 S in in vitro and in vivo experiments.…”
mentioning
confidence: 99%